IMF Survey, Volume 30, Issue 10. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2001)
The IMF's Executive Board on May 15 approved an augmentation of Turkey's three-year Stand-By Arrangement by SDR 6.4 billion (about USD 8 billion), bringing the total to SDR 15 billion (about USD 19 billion). The full text of Press Release 01/23, including details of Turkey's economic program, is available on the IMF's website (www.imf.org).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet